Prevalence of Depression in Type 2 Diabetes Patients in Iran: A Systematic Review - Sahel Eskandari; Mehdi Mohsenzadeh; Ali Asghar Khaleghi; Masoud Mohammadi (Hamadan University of Medical Sciences, 2024)
Background and Objective: Diabetes Mellitus is known as one of the most common chronic metabolic diseases worldwide, so the aim of this systematic review is to determine the prevalence of depression in people with type 2 diabetes. Materials and Methods: This study is a systematic review and metaanalysis by examining Scientific Information Database (SID), Medline (PubMed), ScienceDirect and Google Scholar without time limit starting until May 2023. Results: the prevalence of depression in type 2 diabetes patients in Iran was reported to be 51.7% (CI: 44.4-59, 95%). With the increase in the sample size, the prevalence of depression in sufferers increases (P<0.001) and with the increase in the years of studies and the age of pregnant women, the prevalence decreases (P<0.001). Conclusion: The results of the present study show that the prevalence of depression in people with type 2 diabetes in Iran is at a high level, and it is necessary for the purposeful implementation of preventive measures and to reach lower levels, the attention of health policymakers to the quality of life of people with diabetes and also mental problems and their behavior should be directed in addition to therapeutic measures.